IMPLEMENTASI CUSTOMER RELATIONSHIP MANAGEMENT PADA PELAYANAN JASA SERVICE GADGET ONLINE BERBASIS WEB. (STUDI KASUS DI BROSERVICE KUNINGAN) - Erlan Darmawan; Mochamad Widya Nurahman; Dadan Nugraha (Cloud Information, 2020)
Today business works not only in the trade of goods but also sale services in the real world the visible physically alone, business is mostly done through online media with platform website, The company has not only website but also it applies CRM ( Customer Relationship Management ) with the aim of enhancing value of enterprise in the sight of the customer. Broservice is one of company that engages in servicing gadgets (smartphone, tablet and action camera) that opens stalls online on instagram. Now broservice customers complain about income that are still minimal, and the process of recording data services still simple and communication to customer use application chat whatsapp. The difficulty of broservice in convincing new customers is that they have not been having website. To solve the problem, the writer made a solution that is most effective namely the implementation of customer relationship management on the online services of gadgets web-based. The construction of this system aimed to ease the service and management of data customers in broservice. And they are saving the time, and the information is faster, right, accurate and quality. System made in a Rational the Unified Process (RUP), a system design web-based and use application supporting as XAMPP, programming language design uses language HyperText PreProcessor (PHP) and a user interface the design and DBMS (Database Management System) using MySQL.